The impact of mean body mass index on reported mortality from COVID-19 across 181 countries - Gabbrielli, Ruggero; Pugno, Nicola Maria (Frontiers in Public Health, 2023)
Accountability for global health issues such as a pandemic and its devastating consequences are usually ascribed to a virus, but a comprehensive view should also take into account the state of the host. Data suggests that excessive nutrition is to blame for a yet unknown but not negligible portion of deaths attributed to severe acute respiratory syndrome coronavirus 2. We analysed the correlation between mean body mass index (BMI) and 2-year coronavirus disease 2019 (COVID-19) mortality rates reported by 181 countries worldwide. Almost two thirds of the countries included had a mean BMI greater or equal to 25, with death rates ranging from 3 to 6280 per million. Death rates in countries with a mean BMI below 25 ranged from 3 to 1533. When the analysis was restricted to countries where the extent of testing was deemed more representative of actual mortality, only 19.8% had a mean BMI<25 but the mortality difference persisted. A second analysis looking at pre-vaccination mortality obtained from a different source led to similar conclusions. Due to the nature of the variables, reverse causation can be excluded while common causation can not. A mean BMI<25 for a country seems to spare its citizens from the highest COVID-19 mortality rates. The impact of excess weight on global COVID-19 mortality is suspected to have been much higher than what currently perceived, here estimated at no less than fourfold. Countries with normal mean BMI constitute precious test beds for the quantification of the effects of overeating on COVID-19 mortality.